Geochemical Composition of Surface Sediments in the Bashang Area, North China and its Environmental Significance - Liu, Linjing; Jiang, Gaolei; Mao, Xin; Zhao, Hongmei; Zhao, Yongjie; Li, Yuecong; Zhao, Hua; Bi, Zhiwei (Frontiers in Earth Science, 2022)
The geochemical characteristics of sediments are important for reconstructing paleoclimatic and paleoenvironmental conditions in the marginal area of the Asian summer monsoon. However, robust reconstructions require an understanding of the key factors and mechanisms governing the spatial variations in the composition and ratio of chemical elements in the modern sediments of the marginal area of the Asian summer monsoon. In this study, 128 surface sediment samples were collected from the Bashang area situated in the marginal area of the Asian summer monsoon and examined for their major and trace element contents and grain size. Our results showed that the Rb/Sr ratios of surface sediments in the Bashang areas are more easily affected by other non-climatic factors than the chemical index of alteration (CIA). In addition, SiO2/Al2O3 and Zr/Ti ratios have good positive relationships with the coarse-grained fraction of sediments and thus can be used as proxies for grain size. The exact environmental significance indicated by these proxies should be stated explicitly before using them as proxies for paleoenvironmental reconstructions of the marginal area of the Asian summer monsoon.